2014
DOI: 10.1038/ncomms4199
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α blockade induces IL-10 expression in human CD4+ T cells

Abstract: IL-17+ CD4+ T (Th17) cells contribute to the pathogenesis of several human inflammatory diseases. Here we demonstrate that TNF-inhibitor (TNFi) drugs induce the anti-inflammatory cytokine IL-10 in CD4+ T cells including IL-17+ CD4+ T cells. TNFi-mediated induction of IL-10 in IL-17+ CD4+ T cells is Treg/Foxp3 independent, requires IL-10 and is overcome by IL-1β. TNFi-exposed IL-17+ CD4+ T cells are molecularly and functionally distinct, with a unique gene signature characterised by expression of IL10 and IKZF3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 59 publications
(69 reference statements)
11
104
3
2
Order By: Relevance
“…9a, b), and in addition to this, mice lacking Blimp1 specifically in T cells exhibited significantly higher levels of serum TNF, antigen-specific TNF production, as well as higher frequencies of TNF-producing CD4 + T cells in both the spleen and liver (Fig 2e, 3e, 4a, 4c). A recent study demonstrated that TNF blockade induced IL-10 expression in human CD4 + T cells 382 , supporting earlier reports of IL-10 mediated regulation of TNF 383,384,385 .…”
Section: Blimp1 Deficiency In Treg Cells Does Not Influence Parasite supporting
confidence: 66%
“…9a, b), and in addition to this, mice lacking Blimp1 specifically in T cells exhibited significantly higher levels of serum TNF, antigen-specific TNF production, as well as higher frequencies of TNF-producing CD4 + T cells in both the spleen and liver (Fig 2e, 3e, 4a, 4c). A recent study demonstrated that TNF blockade induced IL-10 expression in human CD4 + T cells 382 , supporting earlier reports of IL-10 mediated regulation of TNF 383,384,385 .…”
Section: Blimp1 Deficiency In Treg Cells Does Not Influence Parasite supporting
confidence: 66%
“…The transcription factor IKZF3/ Aiolos is upregulated in Th17 cells upon TNF inhibition [75]. IKZF3 expression correlates with IL-10 expression in these cells and overexpression of IKZF3 in CD4+ T cells upregulates IL-10 [75]. Collectively, these data suggest that interruption of TNFα signalling induces IKZF3 in Th17 cells resulting in increased expression of IL-10.…”
Section: What Is the Primary Source Of Il-17 In Pso And Psa?mentioning
confidence: 83%
“…IL-10 expression is increased in human Th17 cells following in vitro culture with TNFα inhibitors and in vivo on commencement of TNF inhibitor therapy [75]. The transcription factor IKZF3/ Aiolos is upregulated in Th17 cells upon TNF inhibition [75]. IKZF3 expression correlates with IL-10 expression in these cells and overexpression of IKZF3 in CD4+ T cells upregulates IL-10 [75].…”
Section: What Is the Primary Source Of Il-17 In Pso And Psa?mentioning
confidence: 98%
See 1 more Smart Citation
“…Unexpectedly, these T cells did not have typical Treg markers; therefore TNF-α blockade may also act by promoting suppressor function in non-Treg CD4 + populations [78]. Recent human studies have reflected this finding, showing that TNF-α blockers can induce immunosuppressive features in Th17 cells [79]. …”
Section: Translation From Mouse To Humanmentioning
confidence: 99%